INSTITUTE FOR FORENSIC PSYCHIATRY SOKOLAC: English - Trifković, Ljubiša (Engrami, 2024)
Although it began its official work less than a decade ago, the idea of establishing the Institute for Forensic Psychiatry arose in the seventies of the last century, when a department for forensic psychiatry was formed in the Sokolac Psychiatric Hospital, where patients are placed for the execution of security measures of mandatory custody and psychiatric treatment. . The building where the Institute is located today was built in the early 90s of the last century, but due to the outbreak of the civil war in Bosnia and Herzegovina, it was not put into operation. The institute was officially opened in 2014, and the funds for the reconstruction and equipping of the facility were provided by the Government of Switzerland and through the Ministry of Justice of Bosnia and Herzegovina. The Institute of Forensic Psychiatry in Sokolac is the only institution of this type in Bosnia and Herzegovina, and as such it is a reference institution for scientific research in the field of forensic psychiatry, and a center for the education of medical students, undergraduate and postgraduate studies, and psychiatry residents.
Keywords: institute; forensic; psychiatry; Sokolac; Bosnia and Herzegovina